2012
DOI: 10.1007/s12040-012-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Tidal and gravity waves study from the airglow measurements at Kolhapur (India)

Abstract: Simultaneous photometric measurements of the OI 557.7 nm and OH (7, 2) band from a low latitude station, Kolhapur (16.8 • N, 74.2 • E) during the period 2004-2007 are analyzed to study the dominant waves present in the 80-100 km altitude region of the atmosphere. The nocturnal intensity variations of different airglow emissions are observed using scanning temperature controlled filter photometers. Waves having period lying between 2 and 12 hours have been recorded. Some of these waves having subharmonic tidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…However, Lopez-Gonzalez et al (2005) observed VW values to be approximately −10 km deduced from their OH observations, which do not agree with our values. Further, Ghodpage et al (2012) analyzed the long-term nocturnal data of 2004-2007 and also observed that the VW lies between 28.6 and 163 km. Recently, Ghodpage et al (2013) studied the simultaneous mesospheric gravity wave measurements in the OH emission from Gadanki and Kolhapur, inferring mean VW values varying from −26 to −60 km for the Kolhapur observations.…”
Section: Resultsmentioning
confidence: 99%
“…However, Lopez-Gonzalez et al (2005) observed VW values to be approximately −10 km deduced from their OH observations, which do not agree with our values. Further, Ghodpage et al (2012) analyzed the long-term nocturnal data of 2004-2007 and also observed that the VW lies between 28.6 and 163 km. Recently, Ghodpage et al (2013) studied the simultaneous mesospheric gravity wave measurements in the OH emission from Gadanki and Kolhapur, inferring mean VW values varying from −26 to −60 km for the Kolhapur observations.…”
Section: Resultsmentioning
confidence: 99%
“…The inhomogeneity in electron density present in the atmosphere can develop in to positive streamers at lower (E < E k ) electric fields Kosar et al, 2012). Such inhomogeneity may arise due to meteor trails (Zabotin and Wright, 2001), electrodynamic effects of thunderstorms (Singh et al, 2011b), gravity wave breaking (Fadnavis et al, 2009;Ghodpage et al, 2012).…”
Section: Spritesmentioning
confidence: 99%
“…Solar tides are thermally forced atmospheric oscillations propagating upward with its amplitude growing exponentially with altitude in response to the decrease of the atmospheric density (Chapman and Lindzen, 1970;Sentman et al, 2003;Sao Sabbas et al, 2009;Ghodpage et al, 2012). Gravity waves generated in the troposphere by strong orographic forcing (Jiang et al, 2004;Ghodpage et al, 2012Ghodpage et al, , 2015, deep convection (Fritts and Alexander, 2003), frontal acceleration and geostrophic adjustments (Ford et al, 2000) etc may propagate upward up to the lower thermosphere. At tropical latitudes deep convection associated with severe thunderstorms is found to be a source of broad spectrum gravity waves observed at mesospheric heights Sao Sabbas et al, 2009;Vadas et al, 2009).…”
Section: Elvesmentioning
confidence: 99%